Germ cell cysts, a fetal feature in mammals, are constitutively present in the adult armadillo. Issue 1 (20th November 2019) - Rossi, Luis Francisco; Nottola, Stefania; Miglietta, Selenia; Macchiarelli, Guido; Luaces, Juan Pablo; Merico, Valeria; Merani, Susana; Garagna, Silvia; Zuccotti, Maurizio
Abstract: Formation and subsequent break down of ovarian germ cell (GC) cysts is a key and an evolutionary‐conserved developmental event, described in phylogenetically diverse species of invertebrates and vertebrates. In mammals, cyst break down (CBD) ends at the time of, or soon after, birth with the formation of primordial follicles enclosing single oocytes, which constitute the sole reservoir of gametes available through the whole female's reproductive life. In this study, we challenge this paradigm demonstrating the constitutive presence of a large number of cysts, enclosing two‐thirty GCs, in the ovary of the adult armadillo Chaetophractus villosus, belonging to the superorder Xenarthra, one of the earliest offshoots among placentals. We also describe that (a) GCs enclosed within cysts are connected by intercellular bridges—intercellular bridges—markers of their clonal origin; (b) CBD occurs through four main phases, ending with primordial follicles containing single oocytes; (c) GCs encompass meiotic prophase I stages, from leptotene to diplotene; (d) seasonal variations in the number of GCs enclosed within cysts, suggesting the presence of a GC multiplying activity. The armadillo C. villosus ''s ovary emerges as an extraordinary resource to investigate folliculogenesis and to explore the evolutionary past of the mammalian ovary. Abstract : In mammals, cyst break down ends at the time of birth with the formation of primordial follicles enclosing single oocytes, which constitute the sole reservoir of gametes available through the whole female's reproductive life. In this study, we challenged this paradigm demonstrating the constitutional presence of a large number of cysts, enclosing two‐thirty germ cells, in the ovary of the adult armadillo Chaetophractus villosus, belonging to the superorder Xenarthra, one of the earliest offshoots among placentals.